2001
DOI: 10.1248/bpb.24.876
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and Mitochondrial Damage in INS-1 Cells Treated with Alloxan.

Abstract: A variety of mechanisms have been identified as responsible for the onset of diabetes mellitus. Alloxan shows a selective cytotoxicity on pancreatic b-cells and thus causes insulin-dependent (type I) diabetes mellitus. Although the mechanism of alloxan cytotoxicity is not yet clearly understood, several researchers 1,2) demonstrated that the diabetogenic action was initiated by the generation of reactive oxygen species (ROS). Alloxan is a mild oxidant and is easily reduced to alloxan radicals (A· Ϫ ) by GSH or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 41 publications
3
44
0
2
Order By: Relevance
“…Our interpretation of the higher insulin levels is that b-cell loss by apoptosis is lowered by scavenging ALX-induced ROS, consequently retarding DNA fragmentation and, thus delaying b-cell loss. Sakurai et al also reported that vitamin E and butylated hydroxyanisol significantly prevented the inhibition of glucose-stimulated insulin release by treatment with 0.3 mM ALX (Sakurai et al 2001). Other agents, including Ganoderma lucidum polysaccharides isolated from the fruiting body of a medicinal mushroom (Zhang et al 2003) and red grape seeds proanthocyanidins (El-Alfy et al 2005) are also reported to function as free radical scavengers in ALX-induced diabetic animals.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our interpretation of the higher insulin levels is that b-cell loss by apoptosis is lowered by scavenging ALX-induced ROS, consequently retarding DNA fragmentation and, thus delaying b-cell loss. Sakurai et al also reported that vitamin E and butylated hydroxyanisol significantly prevented the inhibition of glucose-stimulated insulin release by treatment with 0.3 mM ALX (Sakurai et al 2001). Other agents, including Ganoderma lucidum polysaccharides isolated from the fruiting body of a medicinal mushroom (Zhang et al 2003) and red grape seeds proanthocyanidins (El-Alfy et al 2005) are also reported to function as free radical scavengers in ALX-induced diabetic animals.…”
Section: Discussionmentioning
confidence: 91%
“…In turn, such oxidative stress, contributes to b-cell dysfunction and death resulting in the development of diabetes mellitus (Eizirik and Darville 2001;Curtin et al 2002). Taken together, the data indicate that apoptosis is the main mode of pancreatic b-cell destruction (Cnop et al 2005;Kay et al 2000;Jörns et al 2005;Sakurai et al 2001). It is known that DNA fragmentation is preceded by single-strand nicking in apoptosis.…”
Section: Discussionmentioning
confidence: 95%
“…Alloxan induced diabetes produces selective cytotoxicity in β-cells of pancreas through the generation of free radicals resulting in reduced synthesis and release of insulin (Sakurai et al, 2001). In acute study, mastic gum showed significant decrease in blood glucose that was comparable to glibenclamide by rapid normalization of blood glucose levels while high glucose level was observed in alloxan-treated groups throughout the total time period of study.…”
Section: Discussionmentioning
confidence: 90%
“…As is known, alloxan increases production of reactive oxygen species (ROS) leading to cytotoxicity in pancreatic β-cells, and thereby inhibits insulin activity while affecting major organs and haemopoietic system (Sakurai et al, 2001;Sabu et al, 2002). Additionally, alloxan impairs endothe -lium-dependent vasorelaxation and increases contractile responses to agonists such as phenylephrine and 5-HT (Gokce and Haznedaroglu, 2008).…”
Section: Discussionmentioning
confidence: 99%